New Method for Dynamic Tribological Test of Engineering Polymers - Ádám Sarankó; Róbert Keresztes; Gábor Kalácska (International Journal of Engineering and Management Sciences, 2018)
In this article, tribological tests of Polyamide 6 (PA 6), Ultra High Molecular Weight Polyethylene (UHMW PE) and Polyoxymethylene copolymer (POM C) by a new testing method is introduced. The tribometer used in the test is capable for pin-on-disc measuring within all possible layout known in tribology practice, otherwise can be modified into special model of fatigue sliding test. The pin was a specimen made from examined materials, always in contact with a rotating metal disc under a normal load, which is usually static. However, since vibration exists in every practical scene as an important phenomenon, for instance in turning process, we added vibration load into the test. The supplement load is generated by a special-designed vibrating machine. Then properties of examined materials can be studied more profoundly under vibration load. As a result, different value of friction coefficient in static and vibration load have been discovered and taken into comparison.